Kyol Goeu (‘Wind Overload’) Part II: Prevalence, Characteristics, and Mechanisms of Kyol Goeu and Near-Kyol Goeu Episodes of Khmer Patients Attending a Psychiatric Clinic - Hinton, Devon (2001)
Kyol goeu (literally, ‘wind overload’) is an orthostatically triggered syncopal syndrome often found among Khmer refugees in the US. In the present study, 36 of 100 (36%) Khmer patients attending a psychiatric clinic were found to have suffered a kyol goeu episode in the past, whereas 60 of 100 (60%) patients had experienced a near-kyol goeu event in the last six months. Following a survey-based characterization of kyol goeu, as well as the presentation of case vignettes, the article discusses six mechanisms resulting in the high prevalence of the syndrome. The article concludes by comparing kyol goeu and ataque de nervios.